2014
DOI: 10.1186/1477-7517-11-17
|View full text |Cite
|
Sign up to set email alerts
|

‘South Asian cocktail’ - the concurrent use of opioids, benzodiazepines and antihistamines among injecting drug users in Nepal and associations with HIV risk behaviour

Abstract: BackgroundData of the Central Bureau of Statistic of Nepal from 2008 show a total of more than 46,000 illegal drug users, out of which 61% are injecting drug users (IDU). An injecting mix of medicines like opioids, benzodiazepines and antihistamines (the so-called South Asian cocktail) was prevalent. Furthermore, it is estimated that about 70,000 people are living with human immunodeficiency virus (HIV). The government of Nepal has started realizing and recognizing drug use and HIV as significant health and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
(7 reference statements)
0
14
1
Order By: Relevance
“…While there have been reports of nonmedical use of promethazine in combination with opioids from the US [23, 24], India [44], Vietnam [45], and Nepal [46], this, as well as nonmedical use of other prescription antihistamines (hydroxyzine and alimemazine), was uncommon in the present study, in combination with opioids or by itself. However, lifetime medical use of prescription antihistamines was high, reflecting that these drugs are commonly prescribed in Swedish medical care.…”
Section: Discussioncontrasting
confidence: 57%
“…While there have been reports of nonmedical use of promethazine in combination with opioids from the US [23, 24], India [44], Vietnam [45], and Nepal [46], this, as well as nonmedical use of other prescription antihistamines (hydroxyzine and alimemazine), was uncommon in the present study, in combination with opioids or by itself. However, lifetime medical use of prescription antihistamines was high, reflecting that these drugs are commonly prescribed in Swedish medical care.…”
Section: Discussioncontrasting
confidence: 57%
“…Earlier studies have examined the use of prescription tranquilizers (benzodiazepines) among people using drugs, but have mostly focused on opiate users (heroin users and methadone maintenance clients) in different parts of the world (Forsyth, Farquhar, Gemmell, Shewan & Davies, 1993;Fountain, Griffiths, Farrell, Gossop & Strang, 1999;Gelkopf, Bleich, Hayward, Bodner & Adelson, 1999;Iguchi, Handelsman, Bickel & Griffith, 1993). More recent studies have explored complex patterns of prescription and street drug co-use that include prescription opioids (PO) and a variety of PM in adolescent populations (Boyd, McCabe, Cranford & Young, 2006;McCabe, & Cranford, 2012;McCabe, West & Boyd, 2013), persons who inject drugs (Courtney, Degenhardt, Bruno, Roxburgh, & Jenkinson, 2004;Johnson, Fibbi, Langer, Silva & Lankenau, 2013;Lankenau et al, 2007;Lankenau, Teti, Silva, Bloom, Harocopos, & Treese, 2012b;Lankenau & Schrager et al, 2012;Ojha, Sigdel, Meyer-Thompson, Oechsler & Verthein, 2014), college students (Quintero, Peterson, & Young, 2006;Quintero, 2009;McCabe, Teter, & Boyd, 2006;Rabiner, Anastopoulos, Costello, Hoyle, McCabe & Swartzwelder, 2009;White, Becker-Blease, & Grace-Bishop, 2006), nightclub goers (Kelly, Welles, Pawson, LeClair & Parsons, 2014;Kurtz, Surratt, Levi-Minzi, & Mooss, 2011) and men who have sex with men (Benotsch, Martin, Koester, Cejka & Luckman, 2011;Kecojevic et al, 2014, Kecojevic, Corliss & Lankenau, 2015Kelly & Parsons, 2013). Only a few studies have focused on PWUC, and those almost exclusively examined PO misuse (Bruneau et al, 2012;Roy, Arruda & Bourgois, 2011;Roy, Richer, Arruda, Vandermeerschen, & Bruneau, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nonmedical use of promethazine has also been reported among heroin injectors in Vietnam who used it to augment an inadequate heroin dose (Clatts et al, 2010) and among individuals that abuse buprenorphine in India (Singh et al, 1992; Sharma and Mattoo, 1999). Recently, it was reported that the “South Asian Cocktail” which contains buprenorphine, diazepam, promethazine, and/or other substances, is the predominant drug of choice in Nepal (Ojha et al, 2014). Nonmedical use of promethazine has also been reported in other areas of the United States, Hong Kong, and India (Wairagkar et al, 1994; Lam et al, 1996; Shek and Lam, 2006; Agnich et al, 2013).…”
Section: Introductionmentioning
confidence: 99%